Napędy indukcyjno-dynamiczne łączników prądu stałego współpracujące z komorami próżniowymi prądu przemiennego - Rodak, Michał (Wydawnictwo Politechniki Łódzkiej, 2021)
W monografii przedstawiono sposób dobrania parametrów wchodzących w skład próżniowego członu łączeniowego z napędem indukcyjno-dynamicznym, stosowanego jako główny element łączeniowy w łącznikach wykorzystujących technologię próżniową. Głównym zagadnieniem była współpraca NID z komorami prądu przemiennego mogącymi brać czynny udział w wyłączaniu obwodów prądu stałego. Badania te skoncentrowane były nie tylko na samym napędzie NID, ale przede wszystkim na jego współpracy z pozostałymi elementami ww. członów łączeniowych. Uzyskane wyniki stanowią zbiór uwag i wskazówek przeznaczonych dla projektantów tego typu urządzeń.

The monograph presents the method of selecting parameters of the vacuum contact unit (VCU) consisting of an inductive-dynamic drive (IDD), used as the main components in switches based on vacuum technology. The main issue was the cooperation of IDD with alternating current interrupters that can actively participate in switching off direct current. These studies were focused not only on the IDD drive, but also on its cooperation with other elements of the above-mentioned VCU elements. The obtained results and guidelines are intended for designers of this type of devices. A multi-parameter theoretical analysis of the NID drive was carried out by simulating the magnetic and electrical phenomena occurring in it, depending on its design dimensions. This analysis was conducted on the basis of an axially symmetric 2D model. The influence of the drive dimensions on the force generated by the drive was investigated. The paper presents the developed laboratory stand with the use of the high-speed camera Photron APX, where it was possible to measure displacements and analyze the nature of the movement of the VCU components, as well as to measure the opening time. The cooperation of drives with AC interrupters for 600 A and 1250 A was checked.
Keywords: napędy indukcyjno-dynamiczne; komory próżniowe; prąd przemienny; komory próżniowe prądu przemiennego; łączniki prądu stałego; inductive-dynamic drives; vacuum chambers; alternating current; AC vacuum chambers; DC couplers